How do deep-learning models generalize across populations?: cross-ethnicity generalization of COPD detection - Almeida, Silvia D.; Norajitra, Tobias; Lüth, Carsten T.; Wald, Tassilo; Weru, Vivienn; Nolden, Marco; Jaeger, Paul F.; Stackelberg, Oyunbileg von; Heußel, Claus Peter; Weinheimer, Oliver; Biederer, Jürgen; Kauczor, Hans-Ulrich; et al. (Insights into imaging, 2024)
To evaluate the performance and potential biases of deep-learning models in detecting chronic obstructive pulmonary disease (COPD) on chest CT scans across different ethnic groups, specifically non-Hispanic White (NHW) and African American (AA) populations.